Colombia's Higher Education at Risk: Where are the Students? (2000)
The specialized media on the higher education sector in Colombia speak of the fall in demand. But what does this statement refer to? What do we mean when we talk about the “fall”? Different hypotheses have been tacitly accepted as an explanation, the main ones being demographic changes, rising tuition prices, and a decrease in family income. But how true are they and how much do they impact the fall? This paper establishes a methodology that allows addressing the response through a quantitative approach in the exploratory and descriptive analysis of administrative data from official entities in Colombia. It was found that the hypotheses related to the socio-economic environment and financing better explain the fall and contraction of demand in higher education.